TRIP13/FLNA Complex Promotes Tumor Progression and Is Associated with Unfavorable Outcomes in Melanoma. (11th October 2022) - Lu, Wang; Mengxuan, Zhu; Ming, Ren; Zixu, Gao; Yong, Zhang; Simin, Zhang; Yang, Yang; Leqi, Qian; Kangjie, Shen; Yanlin, Li; Jia, Feng; Yiteng, Ding; et al.
Abstract : Cutaneous melanoma is a high-grade malignant tumor originating from skin melanocytes with high risk of recurrence and metastasis. Further study on the mechanism of melanoma development is urgently needed. Here, we performed a bioinformatic analysis to identify critical genes in melanoma using public datasets in the Gene Expression Omnibus database. Among these differentially expressed genes, thyroid hormone receptor interactor 13 (TRIP13) has been reported to exert an important role in the development of various tumors, while its role in melanoma remains unclear. We selected TRIP13 as a candidate gene for further study. TRIP13 expression in clinical specimens was evaluated by immunohistochemistry, and its association with patient prognosis was analyzed by the Kaplan-Meier method and log-rank test. MV3 and A2058 melanoma cells were transfected with lentiviral vector to overexpress or knockdown TRIP13 expression level, and then, its biological function was studied using a series of in vitro and in vivo assays. RNA sequencing, co-immunoprecipitation, and mass spectrometry were used to identify the underlying mechanism of TRIP13. The results of this study exhibited that TRIP13 expression was upregulated in melanoma tissue compared with normal tissues, and high levels of TRIP13 were closely correlated with poor prognoses of melanoma patients. Elevated TRIP13 promoted the invasion and migration of melanoma cells in vitro and enhanced lung metastasis in vivo, without an influence on tumor growth. Importantly, elevated TRIP13 promoted the epithelial-mesenchymal transition (EMT) of melanoma cells, indicating a higher metastatic potential of these cells. Mechanically, TRIP13 physically interacted with filamin A (FLNA) and then activated the PI3K/AKT pathway to transcriptional activation of EMT-related genes. The present study revealed that TRIP13 is a novel prognostic biomarker and potential therapeutic target for melanoma treatment.